A Parameter and complication to be followed in COVID-19 patients: creatine kinase and rhabdomyolysis - Taş, Nevsun Pıhtılı; Telo, Selda (My University, 2022)
This study aims to reveal the relationship between imaging findings obtained from computed tomography (CT), and CK levels in addition to other biochemical parameters\rin individuals diagnosed with COVID-19. The study also aims to draw awareness to the fact that COVID-19 may have various organ involvements apart from the lung.\rTwo hundred and thirty patients with CT findings indicating COVID-19, and 119 control subjects without COVID-19 diagnosis, who had CT scans for other reasons,\rwere included in this retrospective study. The patients were divided into three groups as those with ground-glass opacity (GGO) on CT, those with signs of consolidation\r(CONS) on CT, and the control group with normal CT findings. Then, the imaging and laboratory findings of the patients were evaluated. Of the CT-positive patients, 113\rwere females and 117 were males. There was no statistically significant difference between the groups in terms of the age variable (p=0.43). Ground-glass opacities were\rfound on CT findings in 113 (32.3%) patients, and consolidation findings were found in 117 (33.7%) patients. Serum CK levels were 162.6 (U/L) (13-765) in the group\rwith GGO while these levels were 162 (U/L) (6-731) in the CONS group and 94.27 (U/L) (11-400) in the normal CT group. CK levels were statistically increased in GGO\rand CONS groups compared to the normal CT group (p=0.000). In the initial admission of the patients with COVID-19 diagnoses, all the laboratory parameters should be\revaluated carefully, and risky patients should be followed up considering complications, such as myositis and rhabdomyolysis that may affect mortality.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Patoloji; Enfeksiyon Hastalıkları; Radyoloji; Nükleer Tıp; Tıbbi Görüntüleme